Ways of technical training perfection in rowing on kayaks - A.N. Kolumbet (Physical Education of Students)
Purpose: to find out the ways of rower’s movements perfection. Material: in the research 114 qualified rowers participated. Results: it was found that every rover has the zones of optimal and critical temp. With linear increasing of rowing temp there happens non-linear change of boat’s speed; of working parameters and efficiency of rower’s movements. The highest values of rowers’ efficiency coefficient were registered in zone of intensity of 70-80% from maximal. With temp’s increasing to maximal boat’s speed stabilizes and efficiency coefficient sharply reduces. At the end of distance we registered confident worsening of rowers’ main coordination elements under influence of rising tiredness. Conclusions: in the process of motor qualities’ training it is necessary to ensure: increase working temp up to critical; restore optimal correlation of technical parameters with every new level of temp.